Calculation of Electron‐Scattering Cross Sections Relevant for Hypersonic Plasma Modeling. Issue 4 (19th August 2016) - Laricchiuta, Annarita; Celiberto, Roberto; Capitelli, Mario; Colonna, Gianpiero
Abstract : Electron‐impact induced, optically allowed excitations to the B 2 Π and C 2 Π states in NO molecule are considered in the framework of the similarity approach, accounting for the non‐adiabatic vibronic coupling perturbing the vibrational progression in the excited states. A model for the coupling is proposed from ab initio electronic structure calculations and theoretical oscillator strengths and Einstein coefficients are estimated for its validation. State‐to‐state and total cross sections are derived and, for the transition from the v ″ = 0 level of the ground state, similarity results well compare with available experiments. Abstract : The dynamics of electron‐NO scattering for the optically allowed excitations to the B 2 Π and C 2 Π states is investigated within the similarity approach, reformulated in order to include non‐adiabatic vibronic coupling effects in the vibrational dependence of the state‐to‐states cross sections.